Study of Patients with Pseudoexfoliation Syndrome Undergoing Manual Small Incision Cataract Surgery in a Teaching Hospital - Ajit K. Joshi; Rasika D. Konduskar; Krishangee Kalita (Delhi Journal of Ophthalmology)
Purpose: To discuss preoperative, intraoperative and postoperative considerations and techniques for manual small incision cataract surgery in pseudoexfoliation (PXF) syndrome. Materials and Methods: This prospective study was carried out in the ophthalmology department of a tertiary hospital from March 2019 to August 2019. Patients with cataract associated with PXF without glaucoma were included in this study. All patients underwent a complete ophthalmologic evaluation, including slit-lamp examination, tonometry, gonioscopy, and ophthalmoscopy before the surgery. Manual small incision cataract surgery(SICS) with posterior chamber intraocular lens were performed by a single surgeon who reported the intraoperative difficulties. Patients were followed up on day 1, day 7 and 1 month when they underwent visual acuity testing, IOP measurement and detailed slit-lamp examination. Results: Study included 25 eyes with PXF undergoing SICS. All cases were above 61 years of age, out of which 64% were females. Morphologically nuclear cataract (52%) was the most commonly observed. The most common intra-operative difficulty was poor pupillary dilation in 36% cases. One patient underwent anterior chamber intraocular lens (ACIOL) implantation and 1 patient underwent scleral fixated intraocular lens(SFIOL) implantation. There was no significant difference in the pre and post operative IOP, but post operative (1 month) intraocular pressure (IOP) was less than pre-op IOP (p=0.4). Post-operatively after 1 month 80% patients had best corrected visual acuity between 6/12 to 6/6. Majority of the patients (84%) had associated systemic illnesses like Diabetes Mellitus, Hypertension and Parkinsonism. Conclusion: The present study highlights the importance of proper preoperative preparation, modification of the intraoperative techniques like sphincterotomy and close postoperative follow-up in cases of PXF syndrome undergoing manual SICS to achieve favorable visual outcomes.